School Curriculum and National Integrity - Khan, Mumtaz; Rasool, Shafqat; Sahito, Zahid Hussain (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of writing this paper is to explain relationship between school curriculum and national integrity that how curriculum ties nation in one unit? This relationship gives birth to a series of questions that link each other for example, how curriculum produces and installs spirit of unity in the nation, whether a change may take place first, in curriculum or in the aims of education. Curriculum is enough to achieve this target alone. What strategy in curriculum development should be adapted? Our school curriculum succeeded in winning national integrity, or not. The paper starts with definition of the term “curriculum” before identifying the areas of concern. The paper will also provide roadmap for national integrity by using the vehicle of curriculum (curricular activities and co-curricular activities).